Retrofitting the MyFord 254S lathe with PLC and SCADA control for spindle motor speed regulation - Tumembow, Moody; Wensen, Harry Oktavianus (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
The MyFord 254S lathe in the Mechanical Engineering Department of Politeknik Negeri Manado (Polimdo) will be retrofitted with new technology or features into the old system, becoming semi-automatic, combining PLC and SCADA technology. This research uses the experimental method, where the author designs by creating a ladder diagram in CX-Programmer software and uploading it to the Omron PLC, whose output will be connected to the Variable Frequency Drive (VFD) to control and drive a 3-phase induction motor as a spindle driver with a single-phase AC input voltage on the VFD. It creates a control design in NB-Designer software to be uploaded to the Omron HMI as a SCADA control display. The ladder diagram programming on the Omron PLC designed with CX-Programmer software includes motor frequency options of 15 Hz (602 rpm), 20 Hz (802 rpm), 25 Hz (1003 rpm), 30 Hz (1204 rpm), 35 Hz (1404 rpm), 40 Hz (1605 rpm), 45 Hz (1806 rpm), and 50 Hz (2006 rpm). As a result of the addition of PLC and SCADA to this lathe machine, the spindle speed can be easily adjusted compared to manual settings, as it only requires pressing on the HMI. Contribution to Sustainable Development Goals (SDGs):SDG 9 – Industry, Innovation, and InfrastructureSDG 4 – Quality EducationSDG 12 – Responsible Consumption and Production